ANALISIS TERHADAP PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA NOMOR 90/PUU-XXI/2023 TENTANG BATAS USIA CALON PRESIDEN DAN CALON WAKIL PRESIDEN - Mustaring, Mustaring; Herman, Herman; Padli, Sul (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2025)
This study aims to analyze two main things: (1) the consistency of the Constitutional Court in deciding cases as reflected in the Constitutional Court Decision Number 29/PUU-XXI/2023, Constitutional Court Decision Number 51/PUU-XXI/2023, Constitutional Court Decision Number 55/PUU-XXI/2023, and Constitutional Court Decision Number 90/PUU-XXI/2023. (2) the legal consequences arising from the Constitutional Court Decision Number 90/PUU-XXI/2023.This study uses a normative legal method with a library research approach, which focuses on the study of the decisions of the Constitutional Court which are the objects of research. In addition, this study also examines various secondary legal sources such as books and scientific journals that are relevant to the topic. The results of the study show that: (1) The Constitutional Court rejected the application in Decisions Number 29, 51, and 55/PUU-XXI/2023 on the grounds that the case was part of an open legal policy. However, in Decision Number 90/PUU-XXI/2023, the Court granted part of the application on the grounds that there was an intolerable injustice, so that the principle of open legal policy was set aside. The difference in approach in these decisions reflects the inconsistency in the considerations of the Constitutional Court. (2) The legal consequences of Decision Number 90/PUU-XXI/2023 are final and binding, which requires a revision of the law by the DPR and the President as well as adjustments to regulations through the General Election Commission Regulation (PKPU). However, considering the principle of non-retroactivity in constitutional law and the complexity of the legislative process, this decision cannot be applied in the 2024 Election and will only apply in the 2029 Election.